(untitled) (World Bulletin of Public Health, 2024)
An urgent problem of evaluating the effectiveness of various therapeutic and surgical approaches in the treatment of any diseases occurring against the background of diabetes mellitus is the experimental formation of a diabetes model that would provide a stable increase in blood glucose levels and allow objective studies to assess the features of the course of various processes against the background of diabetes, and was not accompanied by a high mortality of animals in the stage of development of diabetes mellitus. The aim of this study was to develop a new method for modeling diabetes mellitus in an experiment, which will allow achieving an adequate, easily reproducible model of diabetes with damage to a significant part of beta cells, but the absence of high mortality in laboratory animals by reducing the damaging effect of alloxan. As a result of the research, it was possible to cause a persistent increase in blood sugar levels in experimental animals against the background of destructive processes in the endocrine glands of the pancreas. A new method for the formation of diabetes mellitus has reduced mortality to 5%, which is of great importance in further experimental studies to assess the effectiveness of various methods of treating diseases against the background of diabetes mellitus.